Improving Students’ Academic Achievement in English Subject By Using Jigsaw: (Meningkatkan Prestasi Akademik Siswa di Bahasa Inggris Dengan Menggunakan Jigsaw) - Masbirorotni, Masbirorotni; Wulandari, Okky (Indonesian Educational Administration and Leadership Journal (IDEAL), 2020)
This research aims to investigate the effectiveness of Jigsaw as one of cooperative learning model toward students’ academic achievement in English subject. The respondents were the college students’ major in history who were taking English subject at their first semester, academic year 2018/2019. The study adopted the framework proposed by Kemmis and McTaggart (1988); which consists of planning, acting, ovserving, and reflecting. Two cycles were applied to the class, in which each cicle consisted of two meetings. From the treatments, it was revealed that at the first cycle, only 40% of students passed the minimum standard score of completeness 70. Then, at the second cycle, students’ academic achievement improved significantly. 80% of students pass the minimum standard score of completeness. Moreover, aside of improvement in academic achievement, students also motivated to learn English; during teaching and learning process, they actively participated in discussion. Abstrak. Penelitian ini bertujuan untuk menngetahui efektivitas Jigsaw sebagai salah satu model pembelajaran kooperatif terhadap prestasi akademik siswa dalam mata pelajaran bahasa Inggris. Responden adalah mahasiswa jurusan sejarah yang mengambil mata pelajaran bahasa Inggris pada semester pertama, tahun akademik 2018/2019. Studi ini mengadopsi kerangka kerja yang diusulkan oleh Kemmis dan McTaggart (1988); yang terdiri dari perencanaan, akting, ovserving, dan refleksi. Dua siklus diterapkan ke kelas, di mana setiap siklus terdiri dari dua pertemuan. Dari perlakuan, terungkap bahwa pada siklus pertama, hanya 40% siswa lulus skor standar ketuntasan minimum 70. Kemudian, pada siklus kedua, prestasi akademik siswa meningkat secara signifikan. 80% siswa lulus skor kelengkapan standar minimum. Selain itu, selain peningkatan prestasi akademik, siswa juga termotivasi untuk belajar bahasa Inggris; selama proses belajar mengajar, mereka secara aktif berpartisipasi dalam diskusi.